A Full Spectrum of Interpretation: A Discourse-Historical Analysis of One Community College's Mission Statement. Issue 5 (4th May 2022) - Provost, Adrienne L.; Kohnen, Angela M.
ABSTRACT: This study analyzes the internal and external forces that led to the creation and revisions of a community college's mission statement over the course of its 53-year history. We used discourse-historical analysis to examine published college mission statements, transcripts of interviews with the founding dean of the college, and the college's archives (including meeting minutes, accreditation reports, and other internal correspondence). Emerging findings were further contextualized through additional primary sources. We found that the college's founders were influenced by the humanistic education movement and crafted a mission statement that reflected humanistic ideals of self-actualization and positive growth for the betterment of humanity. This original mission statement was nearly unaltered for the first 15 years of the college's existence. However, external forces, including the rise of neoliberalism within education, led to a complete rewrite of the mission statement. The revised statement, reflecting a neoliberal understanding of the purpose of community college education, remains in place. This study demonstrates the influence of external forces, including those contrary to the college's founding principles, on its mission. Given the fact that community colleges serve a vast majority of disadvantaged students, the impact of neoliberal policy is particularly concerning.